Efforts to Promote Moral Education in The Tapak Suci Student Activity Unit 003 at Muhammadiyah University of Surakarta - Ahmad Muzaki; Mohamad Ali (Dinasti International Journal of Education Management And Social Science, 2024)
Morality is a crucial aspect of contemporary society. The inculcation of moral values can be achieved not only through formal education but also through non-formal education, such as participation in organizations. Organizations serve as a platform for individuals to achieve common goals. The efforts of the Tapak Suci organization in promoting moral education are the main focus of this research. This study employs a qualitative approach, utilizing data collection techniques such as documentation, observation, and interviews. The findings indicate that trainers play a significant role in guiding students or members in instilling moral values. The methods employed include advice, habituation, and role modeling. To effectively implement these methods, appropriate media are needed, which are realized through programs such as short religious talks (kultum), Quran recitation sessions (tadarus), discussions, religious messages (tausiyah), monthly studies, and overnight stays (mabit). These are some efforts in imparting moral education through non-formal education.